Catalyzing inclusivity in higher education and beyond: Insights from action-orientated allyship workshops - Anju Gupta; Payal Bhattad (Social Sciences and Humanities Open)
Action-oriented allyship is critical for advancing diversity, equity, and inclusion (DEI) in higher education. This program evaluation examines three complementary workshops designed to build allyship capacity among distinct stakeholder groups: Faculty Allies (n = 21), STEM Allies: Ambassadors for Change for graduate students (n = 18), and the Allyship Think Tank for community partners (n = 24). Guided by intersectionality and social identity theory, the workshops aimed to enhance participants’ recognition of privilege and bias, strengthen intervention skills, and promote organizational change. Each session utilized active learning strategies such as role-plays, case studies, and self-reflection within a supportive environment. Mixed-methods assessment revealed high participant satisfaction, with 42–88 % rating workshops as very satisfactory, and self-reported increases in confidence identifying bias, applying DEI principles, and implementing allyship strategies. Qualitative analyses highlighted the importance of personal experiences, identity intersections, and actionable approaches to allyship. Findings suggest systematic, evidence-based allyship training effectively prepares diverse groups for DEI advocacy and fosters supportive networks that sustain institutional change. This evaluation provides practical guidance for implementing similar programs and adds to the theoretical understanding of allyship education within higher education.